Lithopedion—A Rock Baby - Pradeep Kumar, Chandandur Nagarajaiah; Sowmya, Jagadish; Manupratap, Narayan; Rajendrakumar, N. L.; Nanjaraj, Chakenalli Puttaraju; Sushma, Hanumanthaiah; Raksha, Allalasandra Ramakrishnaiah; Vinaya, Manohara Gowda; Vasanth Kumar, Lakshman Kumar (Journal of Gastrointestinal and Abdominal Radiology, 2020)
Lithopedion is a rare condition that occurs only in ectopic pregnancy and in <1% of all pregnancies. In this condition, the fetus dies and is not absorbed by the mother’s body but escapes the maternal immunity by forming calcified shell around it. The dead fetus remains in the maternal body for considerable period without complications.
Keywords: calcified fetus; lithokelyphopedion; lithokelyphos; stone child